ANALISA HADIS IKHLAS BERAMAL - Amin, Muhammad (IAIN Padangsidimpuan, 2014)
Every job must begin with intention. The intention should be based on sincerity. Sincere intention is an act that is intended solely for Allah. Sincere intentions get a reward from Allah, otherwise if there is no sincere intention there is no a reward from Allah. Intention locates in the heart, therefore every believer who wants to workÂ should put it in his heart.